Scalable MIMO dual band Wi-Fi antenna - Chan, Chee Kin; Koh, Boon Ping; Wong, Alan (IEEE, 2016)
A novel, planar dipole antenna with a small form factor for wireless local area network (WLAN) operation in both 2.4GHz and 5GHz band is presented. The antenna has a small structure measuring 32.6mm × 5.5mm consisting of two folded monopole patterns printed on a 0.8mm thick FR4 substrate. The antenna was designed in CST Microwave Studio ® and was fed using a 50Ω discrete port model. The results show acceptable input matching across 2.4GHz and 5GHz band when placed in tablet, 2-in-1 and laptop mock chassis. Two similar antennas were placed in the device chassis to simulate a multiple-input-multiple-output (MIMO) setup configuration.